Flood Mitigation Strategies Adopted in Sri Lanka A Review - Sivakumar, S. (International Journal of Scientific and Engineering Research, 2015)
Floods are repeatedly in the headlines of local, national and international media. The problem of floods and their computation is one of the main and most complex problems the hydrologists are facing now. The optimal development of water resources depends to a considerable extent on flood control, design and construction of structural measures and taking proper measures for flood mitigation including non-structural measures like flood plain zoning, flood forecasting and warning, etc. All such hydrologic analysis and design problems require accurate and reliable data for flood estimation using statistical and or deterministic methods. The estimation of design flood for safety of structures has also to take into consideration cost aspects and to avoid over design. This paper discuss issues related to the occurrence and its’ management of floods based on several reviews.
Keywords: Meteorology; Water resource; Flood plain